Reduction of Suicide Ideation by the use of Cognitive Behavioural Therapy and Individual Psychology among Undergraduate Students of University of Cape Coast, Ghana - Adom-Mensah, Benedicta Ama; Omotosho , Joshua A.; Antiri , Kwasi Otopa; Fia , Stephen Doh (Journal of Advanced Psychology, 2023)
Purpose: The purpose of the study was to find out the use of Cognitive Behavioural Therapy (CBT) Individual Psychology (IP) in the reduction of suicide ideation among undergraduate students in the University of Cape Coast. Methodology: It was a quantitative study using the quasi-experimental research design, specifically, the pre-test, post-test and control group design. A total of 30 undergraduate students from four colleges of the University of Cape Coast in the Central Region of Ghana were non- randomly assigned to two treatment groups (CBT and IP) and one control group. Beck Scale for Suicide Ideation was used for the collection of data for the study. Both the descriptive (frequency and percentage) and inferential (dependent samples t-test and independent samples t-test) statistics were used to analyse the data at the alpha level of .05. Findings: The study revealed that CBT and IP are effective in reducing suicide ideation among undergraduate students at University Cape Coast. Unique Contribution to Theory, Policy and Practice: It was recommended that screening for suicide ideation among students be carried out on a regular basis organised by the Counselling Centre. This is with the intention of helping to educate them and creating more awareness on suicide ideation among students thereby bringing in more people per the screening to benefit from the therapies